7x - 3 = 3^44 - 23 x 3 x 5
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: x-4/5=3/7
=>x=3/7+4/5=43/35
b: x+3/7=4/5
=>x=4/5-3/7=13/35
c: 19/20-x=8/5-3/4
=>19/20-x=32/20-15/20=17/20
=>x=2/20=1/10
d: =>4/5*x=2/21
=>x=2/21:4/5=5/42
e: =>x:7/9=6/8
=>x=6/8*7/9=3/4*7/9=21/36=7/12
f: =>x/6=2/3-1/3=1/3
=>x=2
a: x-4/5=3/7
=>x=3/7+4/5=43/35
b: x+3/7=4/5
=>x=4/5-3/7=13/35
c: 19/20-x=8/5-3/4
=>19/20-x=32/20-15/20=17/20
=>x=2/20=1/10
d: =>4/5*x=11/21
=>x=55/84
e: =>x=6/8*7/9=42/72=7/12
f: =>x/6=2/3-1/3=1/3
=>x=2
x - 4/5 = 3/7
x = 3/7 + 4/5
x = 43/35
x + 3/7 = 4/5
x = 4/5 - 3/7
x = 13/35
19/20 - x = 8/5 - 3/4
19/20 - x = 17/20
x = 19/20 - 17/20
x = 2/20 = 1/10
4/5 x X = 6/9 - 4/7
4/5 x X = 2/21
x = 2/21 : 4/5
x =5/42
x : 7/9 = 6/8
x = 6/8 x 7/9
x = 7/12
2/3 - x/6 = 6/18
x/6 = 2/3 - 6/18
x/6 = 1/3
x/6 = 2/6
=> x =2
1. x = 43/35
2. x = 13/35
3. x = 1/10
còn lại tự tính nhá
tui bận òi
\(3\cdot\left(\dfrac{1}{2}-x\right)-5\left(x-\dfrac{1}{10}\right)=-\dfrac{7}{4}\\ \Leftrightarrow-8x=-\dfrac{15}{4}\\ \Leftrightarrow x=\dfrac{15}{32}\)
\(4\left(\dfrac{3}{4}+x\right)-\dfrac{1}{5}=7x-\dfrac{1}{7}\\ \Leftrightarrow3x=\dfrac{103}{35}\\ \Leftrightarrow x=\dfrac{103}{105}\)
\(3\left(\dfrac{1}{2}-x\right)-5\left(x-\dfrac{1}{10}\right)=-\dfrac{7}{4}\)
\(\Rightarrow\dfrac{3}{2}-3x-5x+\dfrac{1}{2}=-\dfrac{7}{4}\)
\(\Rightarrow2-8x=-\dfrac{7}{4}\)
\(\Rightarrow8x=2+\dfrac{7}{4}\)
\(\Rightarrow8x=\dfrac{15}{4}\)
\(\Rightarrow x=\dfrac{15}{32}\)
___________
\(4\left(\dfrac{3}{4}+x\right)-\dfrac{1}{5}=7x-\dfrac{1}{7}\)
\(\Rightarrow3+4x-\dfrac{1}{5}=7x-\dfrac{1}{7}\)
\(\Rightarrow4x+\dfrac{14}{5}=7x-\dfrac{1}{7}\)
\(\Rightarrow7x-4x=\dfrac{14}{5}+\dfrac{1}{7}\)
\(\Rightarrow3x=\dfrac{103}{35}\)
\(\Rightarrow x=\dfrac{103}{105}\)
1: \(\dfrac{4}{23}+\dfrac{5}{21}+\dfrac{1}{2}-\dfrac{4}{23}+\dfrac{16}{21}\)
\(=1+\dfrac{1}{2}\)
\(=\dfrac{3}{2}\)
2: \(\left(\dfrac{1}{3}+\dfrac{12}{67}+\dfrac{13}{41}\right)-\left(\dfrac{79}{67}-\dfrac{28}{41}\right)\)
\(=\dfrac{1}{3}+\dfrac{12}{67}+\dfrac{13}{41}-\dfrac{79}{67}+\dfrac{28}{41}\)
\(=\dfrac{1}{3}\)
a)(x+28):13=25,2
x+28=25,2.13
x+28=327,6
x=327,6-28
x=299,6
b)(7x+6)*5^5=5^8
7x+6=5^8:5^5
7x+6=5^3
7x+6=125
7x=125-6
7x=119
x=119:7
x=17
c)(x-3)^2-23=2
(x-3)^2=2+23
(x-3)^2=25
x-3=5
x=5+3
x=8
d)3^30(x-2)=(3^32-3^31)
3^30(x-2)=3^1
x-2=3^1:3^30
x-2=3-29
x=3-29+2
a: \(\Leftrightarrow3x^3-2x^2+15x^2-10x+3x-2+7⋮3x-2\)
\(\Leftrightarrow3x-2\in\left\{1;-1;7;-7\right\}\)
hay \(x\in\left\{3;1\right\}\)
b: \(\Leftrightarrow2x^5-7x^3+4x^4-14x^2+14x^2-49x+49x-44⋮2x^2-7\)
\(\Leftrightarrow2401x^2-1936⋮2x^2-7\)
\(\Leftrightarrow4802x^2-3872⋮2x^2-7\)
\(\Leftrightarrow2x^2-7\inƯ\left(12935\right)\)
\(\Leftrightarrow2x^2-7\in\left\{1;5;13;65;199;995;2587;12935;-1;-5\right\}\)
\(\Leftrightarrow2x^2\in\left\{8;72;2\right\}\)
hay \(x\in\left\{2;-2;6;-6;1;-1\right\}\)
\(\frac{x-23}{24}+\frac{x-23}{25}=\frac{x-23}{26}\)
\(\Leftrightarrow\frac{x-23}{24}+\frac{x-23}{25}-\frac{x-23}{26}=0\)
\(\Leftrightarrow\left(x-23\right)\left(\frac{1}{24}+\frac{1}{25}-\frac{1}{26}\right)=0\)
\(\Leftrightarrow x-23=0\left(vì\frac{1}{24}+\frac{1}{25}-\frac{1}{26}\ne0\right)\)
\(\Leftrightarrow x=23\)
vậy................
\(\frac{201-x}{99}+\frac{203-x}{97}+\frac{205-x}{95}+3=0\)
\(\Leftrightarrow\left(\frac{201-x}{99}+1\right)+\left(\frac{203-x}{97}+1\right)+\left(\frac{205-x}{95}+1\right)=0\)
\(\Leftrightarrow\frac{300-x}{99}+\frac{300-x}{97}+\frac{300-x}{95}=0\)
\(\Leftrightarrow\left(300-x\right)\left(\frac{1}{99}+\frac{1}{97}+\frac{1}{95}\right)=0\)
\(\Leftrightarrow300-x=0\left(vì\frac{1}{99}+\frac{1}{97}+\frac{1}{95}>0\right)\)
\(\Leftrightarrow x=300\)
vậy..........